Berlin. The Genius of Improvisation. - (:unkn) unknown (DOM publishers, 2021)
Berlin is a city that continues to fascinate. It has a turbulent history and is the capital of two reconciled Germanys; it is an increasingly popular tourist destination and includes affordable living and working spaces for young people, artists, and other creative minds. The metropolis of 3.7 million people is also the scene for large-scale urban and architectural projects, bottom-up schemes, and citizens' initiatives such as communal gardening and cooperative living. Is the miracle of Berlin's success due to its genius of improvisation, that is to say its ability to adapt to a complex past, to invent specific courses of action, to negotiate all manner of different obstacles? Since 2016, Berlin's policymakers have been developing an urban strategy to combat real-estate price increases and gentrification. Another challenge for the city is to adapt to demographic change and the growing number of visitors. More participatory, more equitable, and less favourable to cars: Berlin is well-placed for diverse methods of organisation – public-private partnerships, citizen awareness initiatives, social and economic actions.This book aims to explore the German capital's ability to allow the growth of new ideas and thus to remain a leader in innovation. The processes identified here, and the paradoxes deriving from them, will likely even call into question the methods and strategies being employed in other European cities today.
Keywords: Stadtentwicklung; Städtebauentwicklung; Städtebaupolitik; Kritische Rekonstruktion; Entwicklungsstrategie; Wohnungsbaupolitik; Wohnraumversorgung; Planungsleitbild; Stadtpolitik; Privatinitiative; Baugruppe; Urban Gardening